Corrosion Behavior of Mild Steel in Aqueous Solutions of Ammonium Nitrate - Fachikova, Dimka I. (Archives of Metallurgy and Materials, 2026)
The aqueous ammonium nitrate solutions exhibiting a strong general or local corrosion attack to mild and low alloy steels. The corrosion aggressiveness is higher than nitrate solutions of alkali and alkaline earth metals to the same steels, mainly due to lower pH and complexing properties of NH4+-ions, which facilitates the passage of Fe2+-ions in the medium. Corrosion of iron and mild steel in NH4NO3 solutions have been studied by conventional methods and without providing information about the corrosion products and the probable reactions which control the corrosion processes. In the presented work, using electrochemical, physical, analytical and metallographic methods has been investigated the corrosion-electrochemical behavior of low-carbon mild steel (0.17% С) in aqueous solutions of ammonium nitrate. The corrosion-electrochemical parameters of the steel have been determined depending on the concentration, temperature and pH of the medium, as well the effects of thermal treatments – quenching and tempering at temperatures in the range of 200÷600°С. Under these conditions, the steel shows susceptibility or resistance to stress corrosion cracking (SCC). The corrosion products were determined by a Mössbauer analysis to correlate them with the corrosion behaviors of tested steels.